Possible role of androgen receptor gene in therapeutic response of infertile men with hypogonadotropic hypogonadism. (4th July 2019) - Firouzi, Vida; Borjian Boroujeni, Parnaz; Rokhsat Talab, Zeinab; Mohammadi, Maryam; Sadighi Gilani, Mohammad Ali; Sabbaghian, Marjan; Mohseni Meybodi, Anahita
ABSTRACT: Hypogonadotropic hypogonadism (HH) is defined as a dysfunction of hypothalamic–pituitary–gonadal axis, which causes impairments in gametogenesis, pubertal maturation, and/or secretion of the gonadal sex hormones. Human chronic gonadotropin (hCG) stimulates the Leydig cells of the testis to secrete testosterone, which is essential for spermatogenesis. Testosterone replacement therapy is one of the possible options to manage HH treatment. Given the fact that testosterone functions are mediated via androgen receptor (AR), the aim of the present study was to evaluate whether the CAG/GGN triple repeat expansion in AR gene can modulate the response to hCG and testosterone treatment in HH men. Sixty-two men who diagnosed with HH and treated with testosterone and hCG were assessed after treatment. They were classified into two groups, 31 subjects with a positive and 31 subjects with a negative response to replacement therapy within 12–18 months. Androgen receptor CAG and GGN repeat numbers were measured in both groups by hot start polymerase chain reaction (PCR)-sequencing technique. Subjects who reached complete spermatogenesis showed the 20 and 23 as the median numbers of AR CAG/GGN repeats, respectively. In individuals who did not respond to treatment the median length for both CAG/GGN repeats were 23. The average of CAG repeats was statistically lower in patients who had the positive response in comparison to patients who did not respond to hormone therapy (p < 0.05), but the length of GGN repeats were not statistically different between these groups of patients (p > 0.05). The number of CAG repeats are negatively and signiﬁcantly associated with better hormone therapy response. Our results suggest that the length of CAG repeat polymorphism in AR gene might affect the response to treatment in men suffering from HH, whereas no relationship was found between AR gene GGN repeat polymorphism and testosterone and hCG replacement therapy response. Abbreviations: AR: androgen receptor; FSH: follicle stimulating hormone; Gn: gonadotropins; GnRH: gonadotropin-releasing hormone; hCG: human chronic gonadotropin; HH: hypogonadotropic hypogonadism; LH: luteinizing hormone; PCR: polymerase chain reaction